Experiences of belonging to the creative economy: Narratives from Northern micro-entrepreneurs - Nieminen Lenita; Lemmetyinen Arja (Edward Elgar Publishing, 2022)
The present study reports on how creative and cultural micro-entrepreneurs experience belonging to the local creative economy or whether they identify more with the creative place brand. Furthermore, the study focuses on the micro-entrepreneurs’ social embeddedness in the entrepreneurial process comprising social structures and entrepreneurial networks. We conducted phenomenological interviews with four entrepreneurs representing the areas of heritage, art, design, and creative services and utilized Wenger’s community of practice approach as a lens in the narrative analysis. Theoretically, the study contributes to both place branding and entrepreneurship research. The narratives of micro-entrepreneurs in a province in Finland portray an ecosystem that can be a precursor for a place or city becoming a creative place brand, but, at the point at which they were interviewed, the micro-entrepreneurs did not associate themselves or their enterprises with the creative place brand.
There has not been as extensive a focus on social structures and entrepreneurial networks in the context of culture and creative business as there has in other entrepreneurial contexts. When analyzing how the entrepreneurs perceived their sense of belonging to the creative economy it was obvious that entrepreneurship as such was not the primary feature defining their identity. The micro-entrepreneurs did not refer to themselves as entrepreneurs but described themselves as artists or art lovers.
Keywords: creative economy, place brand, belonging, ecosystem, micro-entrepreneur
A Modern Guide to Creative Economies